Comparative study of cooling performance for portable cold storage box using phase change medium. (1st January 2022) - Ray, Alok K.; Singh, Sumer; Rakshit, Dibakar; Udayraj,
Highlights: Design of cold storage box to store and transport of vaccines. Selection of suitable configuration of vaccine storage box. Cooing duration and cooling efficiency evaluated for different configurations. Dominance of convection compared to radiation is observed. Abstract: The present study numerically investigates the cooling performance of portable cold storage boxes using phase change material (PCM) for safe and secure transportation of vaccines under a controlled temperature range of −55 °C to −40 °C at different ambient conditions. A suitable PCM (SP-50) is identified to comply with the temperature requirement of the cold storage box and a comparative study has been performed between a cuboid and cylindrical configuration having the same volume of the box and PCM. Temporal variation of temperature and liquid fraction during phase change of PCM are demonstrated with the help of CFD analysis. The inside temperature of the cylindrical configuration of the box is found to be 4.03% lower than the cuboid box after 17hrs of cooling duration for an ambient temperature of 45 °C. Cooling efficiency and cooling duration of the cylindrical configuration is 8.7% and 20.4% more than the cuboid one respectively at the ambient temperature of 30 °C. The relative dominance between convection and radiation heat transfer is evaluated at different surfaces for both configurations.